2011
DOI: 10.1038/npre.2011.6059.2
|View full text |Cite
|
Sign up to set email alerts
|

Structures at the Atomic Level of Cobalt, Zinc and Lead Niobates (with an Appendix: Atomic structure of cobalt niobate crystal)

Abstract: The author has found in recent years that bond lengths are exact sums of the radii of adjacent atoms and or ions, where the ions have Golden ratio based radii. This work was prompted by the exciting observation last year of the Golden ratio in the magnetic properties of cobalt niobate. It is shown here that in cobalt and zinc niobates, cobalt, zinc and oxygen ions have Golden ratio based ionic radii, whereas in lead niobate, all atoms have covalent radii. Also, the angles at the single bond oxygen anion and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This surprising result shows that the Golden ratio which manifests in the geometry of many creations in the Universe [4] is right in core of the atom! Thus, the ratio of the electrostatic radii of the electron and proton in the hydrogen atom is the Golden ratio, and an atom is a unique construction of Nature [37][38][39][40][41][42][43][44][45][46][47][48][49]. On finding that the covalent bond length d(HH) between the two hydrogen atoms in the molecule H 2 is the diagonal of a square with the Bohr radius as a side, and since the latter is divided into two Golden sections, a e =a B /φ and a p =a B /φ 2 , pertaining to the electron and proton, d(HH) is actually the sum, d(HH)=2 On subtracting the cationic radius, d(H + ) from the bond length of partially ionic alkali metal hydrides and hydrogen halides, it was found that the alkali metal cations are Golden sections of the respective interatomic distances in the metal lattice and the halogens have their covalent radii (which are half the covalent bond length).…”
Section: Additivity Of Atomic and Ionic Radii In Bond Lengths And Str...mentioning
confidence: 99%
“…This surprising result shows that the Golden ratio which manifests in the geometry of many creations in the Universe [4] is right in core of the atom! Thus, the ratio of the electrostatic radii of the electron and proton in the hydrogen atom is the Golden ratio, and an atom is a unique construction of Nature [37][38][39][40][41][42][43][44][45][46][47][48][49]. On finding that the covalent bond length d(HH) between the two hydrogen atoms in the molecule H 2 is the diagonal of a square with the Bohr radius as a side, and since the latter is divided into two Golden sections, a e =a B /φ and a p =a B /φ 2 , pertaining to the electron and proton, d(HH) is actually the sum, d(HH)=2 On subtracting the cationic radius, d(H + ) from the bond length of partially ionic alkali metal hydrides and hydrogen halides, it was found that the alkali metal cations are Golden sections of the respective interatomic distances in the metal lattice and the halogens have their covalent radii (which are half the covalent bond length).…”
Section: Additivity Of Atomic and Ionic Radii In Bond Lengths And Str...mentioning
confidence: 99%